Analisis Kemampuan Literasi Numerasi dalam Permasalahan Struktur Materi Bilangan Siswa Sekolah Dasar - Siti Sulastri; Ana Fitrotun Nisa; Berliana Henu Cahyani (Jurnal PGSD, 2024)
Numeracy literacy is a person's ability to use mathematical knowledge and skills in processing information from various forms, with the aim to solve daily problems wisely. In education, it is important to develop numeracy literacy skills for students. This research aim to explore students' numeracy literacy in solving structured problems on numbers. The subjects in this research were 28 grade IV students at SD Negeri Candirejo, Ngaglik, Sleman. The research approach is descriptive qualitative. Data collection techniques using tests and interviews. The data analysis technique uses stages of data reduction, data presentation, and drawing conclusions. The results of the research show that students already have good numeracy literacy in solving structured problems with number material, with indicators that students are able to apply various types of numbers and symbols related to mathematics, able to analyze information presented in the form of story questions and tables, and able to describe the results of the analysis to make predictions and make problem-solving decisions. The difficulties experienced were not being able to write mathematical sentences, not being able to complete the stages of working, and not writing conclusions.